Patient Perspectives after Trapeziectomy and Ligament Reconstruction Tendon Interposition: A Qualitative Analysis. Issue 6 (20th September 2022) - Stepan, Jeffrey G.; Rolf, Liz; Zhu, Eric; Brody, Madison; Landau, Andrew J.; Calfee, Ryan P.; Dy, Christopher J.
Abstract : Background: The authors aimed to explore patients' perioperative experience after trapeziectomy and ligament reconstruction tendon interposition through semistructured patient interviews to identify deficiencies in preoperative patient counseling. Methods: The authors conducted semistructured interviews with 14 patients who had undergone ligament reconstruction tendon interposition either 10 to 14 weeks or 9 to 12 months postoperatively at the time of their interview. The semistructured interview guide was developed by a fellowship-trained hand surgeon and a qualitative research specialist to discuss each patient's perioperative experience. Inductive and deductive qualitative coding strategies were used to develop a codebook. All transcripts were then double-coded and discussed to develop recurrent major themes from the patient interviews. Results: The authors' interviews identified three major themes discussed consistently on the patient perioperative experience. First, despite specific counseling about a 3- to 6-month postoperative rehabilitation period, patients were still surprised at the length of the recovery process in regaining function, range of motion, and strength. Second, patients repeatedly outlined that surgery on the dominant hand imparted specific limitations that made the postoperative course difficult. Third, patients discussed the importance of hand therapy both in rehabilitation and in guiding patient postoperative expectations. Conclusions: Preoperative counseling is of vital importance to set patient expectations in terms of overall expected outcomes, but also regarding early limitations, expectations, and overall recovery length. These themes have influenced how we counsel our patients about recovery after thumb carpometacarpal surgery and may help other surgeons identify areas for improvement in their discussions with patients.